Determinan penerimaan daerah dan pertumbuhan ekonomi terhadap pengembangan ekonomi kreatif di Provinsi Jambi - Zamzami, Zamzami; Hastuti, Dwi (Jurnal Paradigma Ekonomika, 2018)
This study aims to analyse: (1) Contribution of regional revenue to economic growth, and analyse the development of regional revenues represented by the development of Local Own-source Revenue (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), Revenue Sharing Funds (DBH) and also analyze the development of the economic growth rate of regencies / cities in Jambi Province. This research is intended to obtain answers to how much influence PAD, DAU, DAK, and DBH influence towards the development of creative regencies / cities in Jambi Province both partially and simultaneously and from all the independent variables to be examined. The results of this study indicate that the highest growth of the processing industry is located in Tanjung Jabung Barat district and the variables that have a significant and significant influence on the processing industry in the Regency / City in Jambi Province.